In situ creation of ZnO@CdS nanoflowers on ITO electrodes for sensitive photoelectrochemical detection of copper ions in blood. Issue 29 (13th July 2021) - Zhang, Sheng; Feng, Luping; Li, Pan; Zhang, Lixiang; Chen, Xi; Chu, Su; Gao, Yuan; Xie, Shujing; Jiang, Jiatian; Wang, Hua
Abstract : Unique ZnO@CdS nanoflowers created in situ on ITO electrodes for selective and sensitive photoelectrochemical detection of copper ions in blood. Abstract : A highly selective and sensitive photoelectrochemical (PEC) detection method has been developed for the analysis of copper (Cu 2+ ) ions using nanoflower-like ZnO@CdS heterojunctions, of which ZnO was first in situ grown onto the indium tin oxide electrodes by a hydrothermal method and then coated with CdS through the chemical bath deposition route. It was discovered that the ZnO@CdS heterojunction so formed could serve as a photosensitive catalyst with improved charge separation for visible-light-driven PEC responses. Enhanced visible-light harvesting of nanocomposites could also be expected with CdS as the visible-light sensitizer. Furthermore, the introduction of Cu 2+ ions could cause a rational decrease in the photocurrents of nanocomposites through the specific interaction between CdS and Cu 2+ ions. A ZnO@CdS heterojunction-based PEC sensor was thereby developed for the detection of Cu 2+ ions in blood in the linear concentrations ranging from 0.50 to 80 nM, with a limit of detection of 0.18 nM. Such a heterojunction-based PEC detection platform constructed using two photocatalytic materials with matched band structures are promising for a wide range of applications for sensing Cu 2+ ions in clinical diagnostics, food monitoring, and environmental analysis.